2018
DOI: 10.1186/s12883-018-1016-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and dysfunctions of iron metabolism in Parkinson disease patients with hyper echogenicity in substantia nigra: a cross-sectional study

Abstract: BackgroundTranscranial ultrasound is a useful tool for providing the evidences for the early diagnosis and differential diagnosis of Parkinson disease (PD). However, the relationship between hyper echogenicity in substantia nigra (SN) and clinical symptoms of PD patients remains unknown, and the role of dysfunction of iron metabolism on the pathogenesis of SN hyper echogenicity is unclear.MethodsPD patients was detected by transcranial sonography and divided into with no hyper echogenicity (PDSN-) group and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…A large prospective study showed that elevated systemic Fe can impair dexterity in healthy elderly men [11]. In PD patients, systemic Fe correlated with brain Fe [12], but less is known about the effects of brain Fe on fine motor functions.…”
Section: Introductionmentioning
confidence: 99%
“…A large prospective study showed that elevated systemic Fe can impair dexterity in healthy elderly men [11]. In PD patients, systemic Fe correlated with brain Fe [12], but less is known about the effects of brain Fe on fine motor functions.…”
Section: Introductionmentioning
confidence: 99%
“…* Jinzhou Tian jztian@hotmail.com severer motor and non-motor symptoms [6][7][8]; however, visual hallucinations (VH), one of the most common psychotic symptoms, which was reported to affect 9.8 to 82.7% of PD population in different stages [9][10][11], in relation to SN, have not been reported before. Our objective is to evaluate the validity of TCS for the diagnosis of PD in Chinese population, and to investigate the correlation of sonographic manifestations with clinical features, especially in VH.…”
Section: Introductionmentioning
confidence: 99%
“…However, excess iron is involved in the formation of free radicals and has been associated with oxidative damage to neuronal or other brain cells . Abnormally increased brain iron has been observed in various neurodegenerative disorders including neurodegeneration with brain iron accumulation (NBIA), Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), multiple sclerosis, Wilson's disease, and amyotrophic lateral sclerosis . During past decades, a great number of studies have focused on addressing whether the abnormally increased brain iron is an initial cause for the development of neurodegeneration and neuronal death.…”
Section: Brain Iron Misregulation Is a Common Pathway In Neurodegenermentioning
confidence: 99%